Pengaruh Pelayanan Keperawatan Terapi ROM Terhadap Kekuatan Otot Dan Fleksibilitas Sendi Pasien Pasca Stroke - Marcal, Amerhensya (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Stroke is one of the most serious health problems in today's modern life. Stroke can cause various levels of disturbance, such as decreased muscle tone, loss of sensibility in some limbs, decreased ability to move diseased limbs and inability to perform certain activities. The purpose of this study was to analyze the effect of ROM therapy services on muscle strength and joint flexibility in post-stroke patients at the Guido Vadalares National Hospital, Timor Leste. The research method used was true experiment with a pretest-posttest control group design. The sample in this study were 80 post-stroke patients using purposive sampling technique. Data collection using observation and questionnaires and data analysis using independent t-test. The results showed that the pre-test in the measurement group which measured muscle strength, most of the respondents had less muscle strength (80%) and in the post-test results, most of the respondents had good muscle strength (70%). The pre-test values in the control group which measured muscle strength showed that most of the muscle strength was lacking (75%) and the post-test values were mostly lacking muscle strength (60%). The pre-test values in the treatment group which measured curvature sent all respondents in the less normal category (100%) and the post-test scores were mostly normal (90%). The pre-test value of the control group which was measured by joint flexibility of all respondents was less than normal (100%) and the post-test value of joint flexibility was less than normal (95%).  The results of the analysis of the muscle strength treatment group pretest p=0.473, posttest p=0.000. In the finely measured group, the pretest value was p=0.881, the posttest value was p=0.000. The conclusion of this study is that there is an effect of ROM therapy services on muscle strength and joint stiffness in post-stroke patients. Keywords: ROM; Muscle Strength; Joint Flexibility;  Stroke